On Certain Aspects of Establishment of Political Science (Journal of Philosophy Culture and Political Science, 2018)
The role of higher education in general and humanitarianization of its content in particular has been increasingly important for younger generations especially given that the nation is undergoing a comprehensive modernization of public conscience. Political science plays a special role for training highly qualified professionals and for bringing younger generations as responsible citizens. Although the research thereon has been increasingly vigorous within international academia, a number of aspects have remained overlooked. In this context, it would be sensible to actualize the distinction of political science among the others and its stance and place as a thought discipline. The article covers the outcomes of the comparative analysis carried out by the authors of those few Kazakh, Russian, and foreign sources in Russian and English languages that are relevant to the subject matter with the emphasis being made on the course books and study materials. The analysis reveals the prevalence of the USA in terms of establishment and development of political science, while there have been little written on the evolution of political science within Moscow State University and on the role of its founder M.V. Lomonosov as well as the other Russian academics. The article is, therefore, to make good such a literature deficit.Key words: political science, education, UNESCO, Lomonosov Moscow State University.